145k views
0 votes
X-(2x+3)
how to solve and why you change the sign for the +3?

User Edwin Diaz
by
4.8k points

2 Answers

6 votes

Answer:

Explanation:

x-(2x+3)

Notice that we can't further simplify the things in the bracket so we should multiply by -1

Technically this is like:

x - 1(2x+3)

-1 times 2x = -2x , -1 times 3 is -3

= x - 2x - 3

= -x - 3

User Ranamzes
by
5.4k points
1 vote

Answer:

-x - 3

Explanation:

x-(2x + 3)

=> x-1(2x + 3)

=> x - 2x - 3

=> -x - 3

Therefore, this is the solution. Hoped this helped.


GeniusUser

User Ricab
by
4.9k points